High-temperature Oxidation of Intermetallics Based on Ti-Al-Si System - Knaislová, Anna; Šimůnková, Vendula; Novák, Pavel (Manufacturing Technology Journal, 2018)
Ti-Al-Si alloys excel with their low density and good resistance against high-temperature oxidation in comparison with so far commonly used nickel alloys. Silicon in Ti-Al-Si alloys has significant positive effect on high-temperature oxidation due to increasing adhesion of oxide layer. The TiAl20Si20 alloy was evaluated as the best alloy from tested ones, because its oxide layer protected very well the basic material and TiAl20Si20 achieved good hardness after 400 hours of annealing.
Keywords: Thermal stability; Parabolic constant; Intermetallics; Reactive sintering